Idolatrous drives in kabbalistic imaginary? On the construction of the «Assembly of Israel» as a divine entity - Mottolese, Maurizio (Nuovo Giornale di Filosofia della Religione (NGFR), 2024)
Elliot R. Wolfson has detected in the kabbalistic tradition an «impulse for idolatry», and has examined some of its major forms. In a critical dialogue with Wolfson’s views, the present inquiry attempts to discern other aspects of the kabbalistic imaginary (especially found in the theosophical literature gravitating around the Zoharic corpus), which might indeed be seen as vehicles of idolatrous drives. It focuses, in particular, on long-term patterns structuring the discourse and practice of Jewish mystical circles, where determined ancient symbols or icons – such as the «Assembly of Israel» – came to be hypostasized, projected in heaven, and charged with supernal qualities. Hence, for instance, the people of Israel could appear as a part of the divinity, somehow linked or coinciding with the immanent or the feminine side of the divine realm. Keywords: Idolatry, Kabbalah, Knesset Yisra’el, Shekhinah, Imaginary, Worship Elliot R. Wolfson ha individuato nella letteratura cabbalistica un «impulso all’idolatria», esaminando alcune forme di questo impulso. In un dialogo critico con le tesi di Wolfson, questo articolo tenta di rintracciare altri aspetti dell’immaginario cabbalistico (specialmente presenti nella letteratura teosofica che gravita intorno al corpus zoharico), i quali potrebbero essere effettivamente considerati veicoli di vettori idolatrici. In particolare, si sofferma su alcuni schemi di lungo periodo che strutturano il discorso e la pratica di circoli mistici all’interno dell’ebraismo, in cui determinati simboli o icone – come l’«Assemblea di Israele» – vengono ipostatizzati, proiettati in cielo e caricati di qualità supreme. Così, ad esempio, la comunità d’Israele poté apparire come parte del divino, in qualche modo connessa o coincidente con il lato immanente o femminile della realtà divina. Parole chiave: Idolatria, Kabbalah, Assemblea di Israele, Shekhinah, Immaginario, Culto